Desempenho a pasto de novilhos mestiços de origem leiteira suplementados com níveis energéticos - Alves, Verônica Auxiliadora (2010)
The objective of this trial was to evaluate the productive and economic performance of dairy crossbred steers, reared on Brachiaria Brizantha pasture that received two levels of energetic supplementation during wet/dry transition and four levels during dry/wet transition seasons. During the wet season, forty-eight milk crossbred steers (Holstein x Zebu), with initial average weight of 123 kg and average age of 10 months were used. The treatments consisted of two levels of energy supplementation, 1% of BW, considered high, and 0.5% of BW, considered medium. During dry season, fortyfour fourteen-month-old milk crossbred steers (Holstein x Zebu) were used. The treatments consisted of two high levels of concentrate (1.6% and 1% of BW) and two medium levels of concentrate (0.8% and 0.5% of BW). The supplementation was composed of ground corn and mineral mixture, with urea addition during dry season. A completely randomized experimental design was used. The means were compared by F test at 5% probability in the first experiment and by Tukey test in the second one. The data were analyzed by SAS (1997). The average daily weight gain and final weight were similar between treatments in wet/dry transition. The thoracic measurement indicates a good ponderal development. Energetic supplementation of crossbred milk steers was economically viable, and the medium level (0.5% of BW) presented higher profitability than the high level (1% of BW). In dry season, the energy supplementation improved daily weight gain and the body measures of growing milk crossbred steers reared on pasture. Body length and scrotal perimeter indicated better body development. Milk crossbred steers supplemented on pasture with energy levels ranging from 0.5 to 1.6% should be commercialized for the price of live animal. And, in this case, the lowest level of supplementation (0.5% of BW) should be used for better profitability.